2022
DOI: 10.1213/ane.0000000000006125
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Diminishes, but Does Not Prevent, Developmental Effects of Sevoflurane in Neonatal Rats

Abstract: BACKGROUND: Sevoflurane (SEVO) increases neuronal excitation in neonatal rodent brains through alteration of gamma aminobutyric acid (GABA)(A) receptor signaling and increases corticosterone release. These actions may contribute to mechanisms that initiate the anesthetic’s long-term neuroendocrine and neurobehavioral effects. Dexmedetomidine (DEX), a non-GABAergic α2-adrenergic receptor agonist, is likely to counteract SEVO-induced neuronal excitation. We investigated how DEX pretreatment may alter the neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…The neurophysiological mechanisms of dexmedetomidine mimic the activation of the brain stem and normal sleep pathways rather than cortical suppression [ 133 ]. It is possible that DEX modulates excitatory glutamatergic signaling [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neurophysiological mechanisms of dexmedetomidine mimic the activation of the brain stem and normal sleep pathways rather than cortical suppression [ 133 ]. It is possible that DEX modulates excitatory glutamatergic signaling [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the rats treated with dexmedetomidine before sevoflurane exposure showed lower levels of seizure-like activity and behavioral deficiencies (evaluated by the Morris Water Maze test and acoustic startle response) compared to those without dexmedetomidine treatment. In addition, the DNA methylation patterns in the hippocampus of dexmedetomidine-treated rats were more similar to the control group (i.e., no sevoflurane exposure), whereas rats exposed to sevoflurane without dexmedetomidine pretreatment had noticeably higher levels of DNA methylation ( 71 ). These findings suggest that dexmedetomidine may reduce sevoflurane-induced epigenetic modifications in DNA methylation, thereby attenuating the long-term impairment in neuronal function.…”
Section: Dexmedetomidine Neuroprotection In Animal Modelsmentioning
confidence: 91%
“…Expanding upon Zhong et al’s study, Yang et al conducted experiments exposing neonatal rats to sevoflurane with or without pre-treatment with dexmedetomidine ( 71 ). They found that the rats treated with dexmedetomidine before sevoflurane exposure showed lower levels of seizure-like activity and behavioral deficiencies (evaluated by the Morris Water Maze test and acoustic startle response) compared to those without dexmedetomidine treatment.…”
Section: Dexmedetomidine Neuroprotection In Animal Modelsmentioning
confidence: 99%
“…The analysis of genome-wide DNA methylation patterns in the hippocampus of adult rats neonatally exposed to SEVO identified 407 differentially methylated regions in 391 genes (differentially methylated genes) [ 317 ]. The overrepresentation analysis of the differentially methylated genes yielded multiple enriched gene ontology (GO) terms that covered a wide array of biological processes ranging from nervous system development and function to regulation of stress responses, metabolic processes, vasculature development, and blood circulation [ 317 ]. By acting via mechanisms that involve epigenetic changes and dysregulation of stress response systems, these findings raise the possibility that early life exposure to GAs may predispose to PND, induced by subsequent exposure to surgery and/or GAs in adulthood.…”
Section: Pathogenesis Of Pndmentioning
confidence: 99%